PELATIHAN PENINGKATAN KEMAMPUAN PENGOLAHAN NILAI SISWA BERBASIS MICROSOFT EXCEL KEPADA GURU SEKOLAH DASAR GUGUS IV KABUPATEN FAKFAK - Deisya Maulida Al HAmid; Marendra Syawani Ali; Otniel Koromath (Aptekmas Jurnal Pengabdian pada Masyarakat, 2020)
Technology in Indonesia has experienced rapid development in various fields including computer technology, which directly requires the world of education to act significantly in adjusting itself to technological developments. This is a prerequisite for implementing the 2013 curriculum, where teachers are required to have knowledge and skills, including skills in utilizing information technology in carrying out learning planning activities, administering student personal data, to calculating student average scores and determining student rankings. Even though in Fakfak training for teachers is quite frequent, they talk more about the competence of the learning process in the classroom and very rarely to touch the administrative skills of teachers, including how to process student scores. Therefore, this computer training activity was initiated to improve the abilities and skills of teachers in order to have job support skills, especially being able to process student grade data based on Microsoft Excel. So inputting, calculating grades as an indication of student achievement, as well as creating a simple student score database can be done by the teacher more precisely, accurately, and efficiently. The target to be achieved from this activity is that thethe teachers are able to operate the Microsoft Excel program, especially in processing student scores data, and applying an assessment method as the main indicator for measuring student ability and achievement